Palacios, Sánchez Gómez and Robinson Abrahams: a Reading of Three Novels that Contribute to the Afro-Colombian Heritage (2023)
The present work is an analysis of three novels that are characterized by the fact that they do not belong directly to the canon of Colombian literature. The experiences of their protagonists are analyzed in a Colombian environment marked by inequality, the surviving in periphery and the  back of opportunities in regions located on the margins (Marmato, Caldas; the banks of the trato  river, in Quibdó; Archipelago of San Andrés). The text contributes to the readings about marginality from the literature in the works of two male authors and a female one identified as Afro-Colombian literature. Finally, this work establishes literary connections to approach dialogues in a geographically and socially rugged country —that it is still unknown in its particularities due to the distances between its territories and its cultures.